THE EFFECTIVENESS OF VIRTUAL MICROTEACHING CLASS IN COVID-19 PANDEMIC TIME - Xavio Jun Nusantara Dharmaa; Agus Sapto Nugrohoa; Prayogo Hadi Sulistioa; Nisa Roiyasa (Linguistics and ELT Journal, 2022)
As a spread prevention of Covid-19 virus, schools must implement their learning process through online from Elementary School up to University including Jenderal Soedirman University. In the Covid-19 pandemic, English Education Department of Jenderal Soedirman University has already implemented Microteaching subject online or using E-Learning with the lecturer. This research uses a statistical calculation and interview data from 21 out of 31 respondents because some students have converted Microteaching credit in exchange of participation in Kampus Merdeka Program. There are 5 variables that influence Virtual Microteaching Class effectiveness. They are Enthusiasm, Learning Media, Learning Material, Task, and Lecturers’ Performance. However, the Enthusiasm variable (P=0.046) and Learning Media (P=0.020) are significant for the effectiveness of virtual Microteaching class. At the same time, other variables such as Learning Material (P=0.213), Task (P=0.166), and Lecturers’ Performance (P=0.166) are not significant for virtual Microteaching class. The effectiveness score of Virtual Microteaching Class for 6th semester students, English Education Department of Jenderal Soedirman University is 71% which means effective. The usage of Google Classroom for Virtual Microteaching Class has some disadvantages such as lack of video meeting features that most of the students need, and late notification caused by internet signal problems. As solutions to solve the problems of using Google Classroom for Virtual Microteaching class, lecturers need to explore the features of Google Classroom, and they are encouraged to use a better platform with a built-in virtual meeting and discussion features that can save large data and be downloaded at any time.